Restoration of the Ultrastructural Integrity of the Dermal Collagen Network by 12-Week Ingestion of Special Collagen Peptides - Dorothee Dähnhardt; Stephan Dähnhardt-Pfeiffer; Dörte Segger; Burkhard Poeggeler; Gunter Lemmnitz (Adis, Springer Healthcare, 2024)
Abstract Introduction This pilot study investigated the effects of a 12-week administration of a nutritional supplement containing special collagen peptides on the structural and molecular properties of the collagen fiber network in the human skin. For the assessments, the suction blister method and electron microscopical comparisons were used. Methods Three suction blisters were generated on the inner forearm of each test subject before and after the 12-week administration of the nutritional supplement. High-resolution scanning electron microscopy (SEM) was employed to meticulously investigate the structural characteristics of the skin's collagen network, including the length and diameter of collagen fibers within the suction blister roof. Furthermore, the analysis included immunohistochemistry and fluorescence light microscopy to study hyaluronic acid within the extracellular matrix. Additional assessments encompassed changes in various epidermal parameters. Nine female participants within the age range of 43.7-61.8 years (mean: 52.5 ± 5.9 years) completed the study in accordance with the study protocol. Results Compared with baseline, the 12-week supplementation regimen led to a statistically significant average increase in the collagen fiber network size of 34.56% (p < 0.0001). Additionally, collagen fiber cross-linking and fiber length were substantially increased. The ingestion of the supplement also resulted in an 18.08% elevation in epidermal hyaluronic acid concentration (p < 0.0001). No adverse events were recorded during the study. Conclusion Using an innovative approach, this study demonstrated the ability of a targeted nutritional supplement to effectively restore the ultrastructural integrity of the dermal collagen network, which is typically disrupted by the natural aging process of the skin. These findings not only corroborate existing data regarding the positive effects of oral collagen peptides on skin structure and function but also contribute to our understanding of ultrastructural morphological aspects of changes in the skin's collagen network. Supplementation can induce regeneration of the collagen fiber network in the human skin. Trial Registration Number German Clinical Trials Register, DRKS-ID DRKS00034161- Date of registration: 06.05.2024, retrospectively registered.